What's Race Got to Do With It? CRP Levels in Immune Mediated Skin Diseases: Considerations for Hidradenitis Suppurativa - Okeke, Chidubem A. V.; Williams, Jonathan P.; Iwuala, Callyn U.; Igwe, Pearl K.; Khanna, Raveena; Perry, Jessica D.; Okoye, Ginette A.; Byrd, Angel S. (Frontiers in Immunology, 2022)
Currently, there is a lack of racial/ethnic heterogeneity in research databases, exposing a systematic issue in studies exploring inflammation-mediated diseases, such as hidradenitis suppurativa (HS). HS is a chronic inflammatory skin condition that disrupts normal structure and functioning of terminal hair follicles, resulting in the formation of recurrent abscesses, nodules, and sinus tracts within intertriginous regions. Studies describe higher serum levels of inflammation-mediated C-reactive protein (CRP) in patients with HS, a disease that predominantly affects skin of color (SOC) populations, Herein, we explore the role of CRP levels in the context of disease presentation, management, and psychosocial implications in SOC patients with HS in order to further address existing health disparities in this population.